Alinhamento estratégico de TI: avaliando as percepções de executivos de negócio e TI - Souza, José Geraldo Andrade de (2008)
The Information Technology (IT) is a concept which has gained importance for organizations. It is expected that the strategic use of IT not only sustain the business operations of enterprises, but mainly leverage the initiative of new competitive strategies. However, these expectations on the earnings with the IT not have been achieved and questions arise about the return of the investments in IT. One of the causes is credited to the lack of alignment between the strategies of business and IT. The search of strategic alignment between IT and business takes to the necessity of measure it. This assessment can help identify whether the perceptions of business executives and IT executives, about the strategic alignment of IT, are similar or different. The objective of this work is to investigate the perceptions of business executives and IT executives in relation to the IT strategic alignment implemented in a selected organization. It was conducted a case study, in a company that provides services to the financial market. As a result, this work identified that there is no statistically significant difference between the perceptions of business executives and IT executives, related to the level of IT strategic alignment maturity implemented in the organization, and highlighted factors that promote this alignment: (a) senior management supports the IT (b) IT takes part of strategic planning, (c) IT understands the business of the company, and (d) there is a partnership between business and IT executives. Additionally, it was proposed that these similar perceptions result from the sharing of assumptions, knowledge and common expectations for the IT strategic alignment between the two groups of executives interviewed, and that led the company to achieve a higher level of IT strategic alignment. Each Practice of Strategic Alignment was examined separately. Although not have statistically significant differences between the perceptions of business executives and IT executives, the practices of Communication, Measures of Value and Competence, and Skills were better assessed by business executives and the practices of Governance and Partnerships have been better perceived by IT executives. The practice of Scope and Architecture and the IT Strategic Alignment, showed no differences in perceptions between the two groups of executives.